Exploring digital art’s role in cultural product innovation in northeast China’s industrial base - Geng, Wei; Liu, Shunli (Edelweiss Applied Science and Technology, 2024)
This research investigates the impact of digital art on the innovation of cultural and creative products, particularly in Northeast China’s historical industrial regions. It explores how digital art enhances product design and functionality, ultimately improving market competitiveness. Data was collected via a questionnaire survey targeting employees in these regions, with SEM used to analyze the relationships between digital art, product innovation, and market competitiveness, focusing on the mediating role of product innovation. The results reveal that integrating digital art significantly enhances market competitiveness by advancing technology, enriching design aesthetics, and aligning products with market demands. Product innovation is identified as a key mediator in this process, underscoring digital art’s essential role in the development of cultural and creative products. The study concludes that digital art not only boosts the artistic quality and market appeal of these products but also drives continuous innovation, positioning it as a vital force in the cultural industry’s growth. As technology advances, digital art is expected to become increasingly influential in shaping the future of cultural and creative sectors.